Adollescent Characteristics Relation with Premarital Sex Attitudes - Irene Febriani; Destinady Kadiser Miden (Institute of Computer Science (IOCS), 2022)
Adolescence is an important part of individual development and begins with the maturity of the physical organs. Adolescents have the opportunity to obtain optimal health status, but adolescent behavior does not always support it. This study aims to analyze the relationship between age, education, gender and welfare with adolescent attitudes about premarital sex and risky behavior. Using secondary data from the 2019 Program Performance and Accountability Survey (SKAP) totaling 316 adolescents by systematic random sampling research design cross-sectional, carried out in 2020 with frequency distribution and chi square test. The results showed that 64.4% did not agree with premarital sex and did not engage in risky behavior. 91.2% of age related to premarital sex (P Value 0.005) and risky behavior (P Value 0.020). Gender is associated with premarital sex attitudes and risky behavior (P value 0.005). Family welfare variables are not related to premarital sex attitudes and risky behavior (P Value > 0.05). The content of information sources still needs to be considered, facilitators who disseminate information sources again need to be given training and the goals for providing information are adjusted and targeted.